Development and Investigation of Mesoporous Bioactive Glass/Zein Coatings Electrodeposited on Titanium Alloy for Biomedical Applications - Maciag, F.; Moskalewicz, T.; Cholewa-Kowalska, K.; Hadzhieva, Zoya; Dziadek, M.; Lukaszczyk, A.; Boccaccini, Aldo R. (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
The objective of the present work was the development of cathodic electrophoretic deposition (EPD) to obtain composite coatings of mesoporous sol-gel glass (MSGG) particles embedded in a zein matrix on Ti-13Nb-13Zr substrates. To deposit robust and repeatable coatings, a direct current EPD and pulsed direct current EPD as well as the deposition kinetics were investigated, including the deposition yield and deposition rate. The stability of the suspension was determined based on the zeta potential and conductivity. Macroscopically homogeneous coatings with a thickness of about 10 mu m and various volume fractions of MSGG were subjected to further examination. Coatings were uniform, exhibiting open porosity and showing excellent adhesion to the substrates. Both zein and MSGG particles revealed an amorphous structure. The coated substrates demonstrated greater resistance to electrochemical corrosion in Ringer's electrolyte in comparison with the virgin (non-coated) substrate. The coatings showed high roughness and moderate hydrophilicity. The incubation of the coated substrates in concentrated 1.5 simulated body fluid (1.5SBF) showed the formation of carbonate hydroxyapatite. The composite coatings showed improved antibacterial properties against gram-negative E. coli and gram-positive S. aureus bacteria compared to pure zein coatings. Electrophoretic MSGG/zein composite coatings should be further investigated in terms of their osteoconductive behavior, to confirm their suitability for medical applications in orthopedics.
CRIS-Team WoS Importer:2022-11-18